GENEOLOGI PEMIKIRAN ABU RAYYAH - Martono, Febriansyah; Saadah, Dadah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
Hadith as a source of Islamic teachings is very open to be studied by many parties. Not only Muslims, even outsiders of Islam also intervened in researching it. One of the groups that contributed to this was the orientalists. Which in the end actually raises doubts in the Muslim body. One of the figures affected is Abu Rayah. Not only from orientalism, with the method of literature study, it was found that his thinking actually adopted orientalism in terms of the position of hadith. While his cynical view of Abu Hurairah, this intersects or is similar to the mindset of the Shia group. The conclusion is that he is equal to other adherents of sunnah disbelief.